Prototype Early Warning System Tanah Longsor Menggunakan Fuzzy Logic Berbasis Google Maps - Novalia Dwirohmatun Sugianti; Ida Bagus Ketut Widiartha; Ario Yudo Husodo (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
Landslide is one of frequent natural disaster in Indonesia that can cause many casualties, damage the buildings, loss of livelihoods, deteriorating sanitation, and the emergence of many diseases. To minimize this, prevention is needed by mapping the landslide prone areas and provided the early warning. This research will test in six areas in Lombok there are Batulayar, Bayan, Tanjung, Gangga, Sambelia, and Sembalun. The variable used are ground height, slope, rainfall, soil type, and land cover. There is a lot of method that can use to mapping such as fuzzy logic. Fuzzy logic is one of method that can mapping the input into the output space. By using fuzzy logic produces a level of accuracy for determining landslide prone areas is 83,3% and for the warning is 91,67%. So that, fuzzy logic can be used to mapping the landslide prone areas and make the early warning sytem.